Idarubicin and Ara-C Treatment Associated with Fungal Infection in Acute Leukemia Patients with Febrile Neutropenia - Wanitpongpun, Chinadol; Teawtrakul, Nattiya; Lanamtieng, Theerin; Chansung, Kanchana; Sirijeerachai, Chittima; Amampai, Worakamol; Sawanyawisuth, Kittisak (Clinical Cancer Drugs, 2021)
Background: Pateints with acute leukemia along with febrile neutropenia is at risk for fungal as well as bacterial infections. Fungal infection is a more serious and common infection in this setting, leading to a high mortality rate. There is limited data on clinical factors predictive of fungal infection in acute leukemia with febrile neutropenia. Objective: This study aimed to evaluate clinical predictive factors of fungal infection in acute leukemia patients with FN. Methods: This was a retrospective analytical study and included adult patients diagnosed with acute leukemia, who developed FN, and had positive culture with either bacterial or fungal infection. Predictors for fungal infection were calculated by using logistic regression analysis. A subgroup analysis in patients with acute myeloid leukemia (AML) was also performed. Results: There were 94 patients who met the study criteria. Of those, 29 patients had positive culture for fungus (30.82%), categorized as Aspergillus (19 patients; 65.51%) and Candida (10 patients; 34.49%). The mortality rate was significantly higher in the fungal infection group than the bacterial infection group (24.14% vs. 6.15%; p 0.031). There were six factors in the final model predictive of fungal infection with one independent predictor: treatment regimen of Idarubicin plus Ara-C with an adjusted odds ratio of 5.188 (95% CI of 1.386, 19.419). A subgroup analysis for fungal infection in patients with AML showed that only the treatment regimen of Idarubicin plus Ara- C was a significant factor. Its adjusted odds ratio was 5.138 (95% CI of 1.156, 24.467). Conclusion: Treatment with idarubicin and Ara-C may increase the risk of fungal infection in acute leukemia patients with FN.
Keywords: Aspergillosis